Volcanic sulfides and outgassing - Edmonds, M; Mather, T (Mineralogical Society of America, 2017)
Sulfides are a major potential repository for magmatic metals and sulfur. In more reduced magmas, there may be a dynamic interplay between sulfide liquids and degassing as magmas ascend/erupt. Sulfide-bubble aggregates may segregate to shallow levels. Exsolved fluids may oxidize sulfides producing SO2 gas and metals, which may vent to the atmosphere with chalcophile metal ratios reflecting those in the sulfide liquids. Sulfide breakdown and/or sequestration timing and balance define the role of sulfides in both ore formation and the environmental impacts of volcanic eruptions, including during Large Igneous Provinces, key periods of heightened volcanism during Earth history.